The impact of dental caries on oral health related quality of life amongst adult population in Lahore, Pakistan - Shahzad, Hazik Bin; Awais, Faiza; Shirazi, Um-e-Rubab; Majeed, Hanna Abdul; Rafique, Aqeela; Shahbaz, Maliha (UI Scholars Hub, 2020)
Background: Dental caries in adults is a public health problem. A comprehensive assessment of the association between caries and Oral Health Related Quality of Life (OHRQoL) measures is essential for understanding how it impacts the daily life of people and for assessing their oral health needs. Methods: The survey was conducted at Rashid Latif Dental Hospital, from March-June 2019. A total of 373 adults aged 18-80 years were randomly enrolled in the study. Dental caries was the main exposure, measured clinically. The OHRQoL was measured through Oral Impacts on Daily performance (OIDP) questionnaire. Caries was dichotomized and the relationship to OHRQoL was determined. Results: The results showed that 87.6% of the people presenting to the hospital had one or more carious teeth. Difficulty eating, and relaxing/sleeping were among the top reported impacts. Adults with caries showed higher odds for reporting higher oral impacts compared to those without caries. For every added carious tooth, there is 1.38 times increase in OIDP score. Conclusion: Individuals with caries were more likely to report more frequent and severe oral impacts that manifested into their daily lives through difficulty eating or relaxing. OIDP score increased linearly with increased exposure to caries.